ANALISIS PERBANDINGAN DEGREE OF FINANCIAL LEVERAGE ANTARA PT. INDOCEMENT TUNGGAL PRAKARSA, TBK DAN PT. SEMEN INDONESIA (PERSERO), TBK - Nining Andriani; M. Rimawan (LP2M Universitas Bina Bangsa, 2023)
One measure or criterion that needs to be considered for companies in using funding sources from bank debt is Degree Financial Leverage (DFL). This study aims to analyze the comparison of Degree Of Financial Leverage Between PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia (Persero), Tbk. The type of research used is comparative research. Quantitative data type, secondary data source. The research instrument used is a table containing data on Earnings Per Share (EPS) for the initial year and Earnings Per Share (EPS) for the final year, data on Earnings Before Interest and Taxes (EBIT) for the initial year and Earnings Before Interest and Taxes (EBIT) for the final year at PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia (Persero), Tbk. The population used in this study is the entire financial statements of PT. Indocement Tunggal Prakarsa, Tbk since it was listed on the IDX from 1998 to 2021, namely for 23 years and PT. Semen Indonesia (Persero), Tbk from 1991 to 2021, namely for 30 years. The sample in this study is the financial statements of PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia (Persero), Tbk for 11 years, from 2012 to 2022. The sampling technique used in this study is purposive sampling technique. The data collection techniques used in this study are documentation and literature studies. The data analysis technique in this study is to use Degree of Financial Leverage (DFL) component analysis and Independent sample test. The results showed that there was no significant difference in Degree Of Financial Leverage between PT. Indocement Tunggal Prakarsa, Tbk and PT. Semen Indonesia (Persero), Tbk